a)390-(x-7)=169:13
<=>390-(x-7)=13
<=>x-7=390-13
<=>x-7=377
<=>x=377+7
<=>x=384
b)x-6:2-(48-24):2:6-3=0
<=>x-3-24:2:6-3=0
<=>x-6-12:6=0
<=>x-6-2=0
<=>x-8=0
<=>x=8
a) 390 - ( x - 7 ) = 169 : 13
390 - ( x - 7 ) = 13
x - 7 = 390 - 13
x - 7 = 377
x = 377 + 7
x = 384
b) x - 6 : 2 - ( 48 - 24 ) : 2 : 6 - 3 = 0
x - 3 - ( 48 - 24 ) : 2 : 6 = 0 + 3 = 3
x - 3 - ( 48 - 24 ) : 2 = 3 x 6 = 18
x - 3 - ( 48 - 24 ) = 18 x 2
x - 3 - 24 = 36
x - 3 = 36 + 24
x - 3 = 60
x = 60 + 3
x = 63
Jang Ha Na làm sai mà cũng đc ****
Bài làm :
a)390-(x-7)=169:13
<=>390-(x-7)=13
<=>x-7=390-13
<=>x-7=377
<=>x=377+7
<=>x=384
b)x-6:2-(48-24):2:6-3=0
<=>x-3-24:2:6-3=0
<=>x-6-12:6=0
<=>x-6-2=0
<=>x-8=0
<=>x=8